CD4(+) T Cells and CD40 Participate in Selection and Homeostasis of Peripheral B Cells - Schwartz, Marc A. (AAI, 2014)
Control of peripheral B cell development and homeostasis depends critically on coordinate signals received through the BAFFRs and BCRs. The extent to which other signals contribute to this process, however, remains undefined. We present data indicating that CD4(+) T cells directly influence naive B cell development via CD40 signaling. Loss of CD4(+) T cells or CD40–CD40L interaction leads to reduced B cell homeostatic proliferation and hindered B cell reconstitution posttransplantation. Furthermore, we demonstrate that in the absence of CD40 signals, these events are modulated by BCR self-reactivity. Strikingly, murine models lacking CD40 reveal a broadly altered BCR specificity and limited diversity by both single-cell cloning and high-throughput sequencing techniques. Collectively, our results imply that any setting of T cell lymphopenia or reduced CD40 function, including B cell recovery following transplantation, will impact the naive B cell repertoire.